The Effect of PITS-Based Education to Enhance Health Literacy on Self-Management in Older Adults with Physical Multimorbidity - Chittarat, Mananchaya; Panuthai, Sirirat; Tamdee, Decha (Nursing Journal CMU, 2023)
Self-management is important behavior for older people with physical multi- morbidity to control their disease. This experimental research aimed to examine the effect of PITS-based education to promote health literacy on self-management among older adults with physical multimorbidity. The sample group included older persons, diagnosed with both diabetes mellitus and hypertension, attending Thungyai district health services in Nakhon Sri Thammarat province. Forty-eight subjects were randomly selected and assigned to either the experimental or control group (24 subjects each). The experimental group received PITS-based education, consisting of four group education sessions and one individual education session over three weeks, while the control group received routine care. The tools used for data collection included 1) a personal and illness data recording form, and 2) the Patient Assessment of Self-Management Tasks questionnaire. Data were analyzed by descriptive statistics, indepen- dent t-test, and dependent t-test. The results revealed that the experimental group, who received PITS-based educa- tion, had a significantly higher self-management mean score than before participating in the intervention as well as a significantly higher mean score than that of the control group (p < .001). Therefore, healthcare providers can apply PITS-based education as a guideline for health education in older persons with physical multimorbidity to improve self-manage- ment.